Interview with the Hon. Ken Wyatt: improving Indigenous health outcomes from a political viewpoint - Ken Wyatt (Sax Institute, 2017)
In 2017, Australia celebrates 50 years since the 1967 referendum, when more than 90% of Australians voted to amend the constitution to allow the national government to create laws for Indigenous people and include them in the census. We spoke with the Honourable Ken Wyatt, the Minister for Indigenous Health and the Minister for Aged Care, about what has occurred over the past 50 years in Indigenous health from a political perspective, and what we have learnt to improve health outcomes in the future.